Kegiatan Marketing Public Relations 150 Coffee & Garden - Pinkan Amanda Salfa; Riza Hernawati (UNISBA Press, 2022)
Abstract. 150 Coffee & Garden is a coffee shop which is located at Jalan Sulaksana No. 50 cities of Bandung. Founded in 2017, 150 Coffee & Garden is loved by all groups, both young and old. By occupying a former confection factory that has been repainded, 150 Coffee & Garden is able to attract consumers’ attention as a family friendly place, because the main product is consumer comfort, so the atmosphere that is always created is a sense of comfort. The pandemic changed the trend of the coffee business in 2021. The coffee shop became one of the places of business that were forced to continue to struggle in the conditions of the Covid-19 pandemic, this made 150 Coffee & Gardens use Marketing Public Relations to build brand awareness during the pandemic. In this study, the authors use qualitative research methods, with a case study approach in order to understand the uniqueness of the object under study. The data collection techniques are using interviews, observations, documentation and written sources. The result of this study, it was found that the concept of 150 Coffee & Garden’s marketing public relations activities started from creating interesting content, using persuasive captions, and holding quizzes on Instagram stories, with a segmentation target of all group. In the marketing public relations strategy, it is in accordance with the concepts made previously. Although there are inhibiting factors but they can be overcome. While the reasons 150 Coffee & Garden uses the family friendly concept as a tagline, 150 Coffee & Garden wants to reach all circles, both young and old create family friendly coffee place (a coffee place that is suitable to be visited with family) Abstrak. 150 Coffee & Garden merupakan sebuah coffee shop yang beralamat di Jalan Sulaksana No. 50 kota Bandung. Didirikan pada tahun 2017, 150 Coffee & Garden banyak disenangi oleh semua kalangan baik anak muda maupun orang tua. Dengan menempati bekas pabrik konfeksi yang telah diperbaiki, 150 Coffee & Garden mampu menarik perhatian konsumen sebagai tempat yang family friendly, karena produk utama adalah kenyamanan konsumen, maka suasana yang senantiasa diciptakan adalah rasa nyaman. Trend bisnis kopi berubah pada masa Pandemi tahun 2021. Coffee shop menjadi salah satu tempat usaha yang dipaksa untuk terus berjuang di kondisi pandemi Covid-19, Hal ini membuat 150 Coffee & Garden menggunakan Marketing Public Relations dalam membangun brand awareness di masa pandemi. Pada penelitian ini, penulis menggunakan metode penelitian kualitatif, dengan pendekatan studi kasus agar dapat memahami keunikan dari objek yang diteliti. Adapun teknik pengumpulan data yaitu menggunakan wawancara, obervasi, dokumentasi dan sumber tertulis. Hasil dari penelitian ini yaitu, ditemukan bahwa konsep kegiatan marketing public relations 150 Coffee & Garden dimulai dari mencari tema untuk konten, dilanjut dengan hunting foto untuk membuat konten yang menarik, serta menggunakan caption yang persuasif. Pada strategi marketing public relations sudah sesuai dengan konsep yang dibuat sebelumnya, walaupun terdapat faktor penghambat tetapi masih bisa diatasi. Sedangkan alasan 150 Coffee & Garden menggunakan konsep family friendly sebagai tagline yaitu, 150 Coffee & Garden ingin meraih semua kalangan baik anak muda maupun orang tua dan menciptakan tempat kopi yang family friendly (tempat kopi yang cocok dikunjungi bersama keluarga)